2013
DOI: 10.3386/w19656
|View full text |Cite
|
Sign up to set email alerts
|

Fostering and Measuring Skills: Interventions That Improve Character and Cognition

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
289
0
13

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(308 citation statements)
references
References 196 publications
6
289
0
13
Order By: Relevance
“…Eight of these interventions (13 percent) were evaluated across multiple school levels (see Figure 5.2). The larger number of evidence-based interventions for elementary schools is con-sistent with other research that has found fewer effects for skills-based, explicit SEL interventions among adolescents than among younger students (Heckman and Kautz, 2013;Yeager, 2017).…”
Section: Evidence Across School Levelsmentioning
confidence: 70%
“…Eight of these interventions (13 percent) were evaluated across multiple school levels (see Figure 5.2). The larger number of evidence-based interventions for elementary schools is con-sistent with other research that has found fewer effects for skills-based, explicit SEL interventions among adolescents than among younger students (Heckman and Kautz, 2013;Yeager, 2017).…”
Section: Evidence Across School Levelsmentioning
confidence: 70%
“…Recent research suggests that noncognitive skills, such as perseverance, empathy, and selfefficacy, remain malleable during adolescence 90 and build on the cognitive skills developed during early childhood. Interventions such as adolescent mentoring, residential training (eg, Job Corps), and workplace-based apprenticeship programs can increase academic achievement, employment success, and other nonacademic accomplishments over the life span.…”
Section: Interventions For Adolescents and Parents Of Young Childrenmentioning
confidence: 99%
“…Interventions such as adolescent mentoring, residential training (eg, Job Corps), and workplace-based apprenticeship programs can increase academic achievement, employment success, and other nonacademic accomplishments over the life span. 90 …”
Section: Interventions For Adolescents and Parents Of Young Childrenmentioning
confidence: 99%
“…Early identification of the personality traits that influence who becomes unemployed may better guide the targets of interventions, such as school and work programs designed to foster the development of particular psychological characteristics (Heckman & Kautz, 2013).…”
mentioning
confidence: 99%